Seniority — Nature and scope of discretion for a company in applying a seniority clause — Power of the board to find against the company

(untitled) (Département des relations industrielles de l’Université Laval, 1961)
SummaryA Company has no absolute right of discretion when applying a seniority clause containing objective criteria for its application in case of short-term lay-offs, otherwise the seniority rights of the employees could be obliterated by Company action.The arbitration board must satisfy itself that the company's administrative act was taken with full appreciation of the right for senior employees to be retained on short-term layoffs provided in the Company's reasonable judgment exerciced with care and in good faith, it is practical to retain themCanadian Industries Ltd. and Le Syndicat des Travailleurs de Produits Chimiques de McMasterville; H.D. Woods, Chairman, Me Raymond Caron, Company's nominee, Me Marc Lapointe, Union's nominee.